Counseling on the Use of Over-the-counter and Limited-Free Medicines for recitation mothers in Cibungur Village, Tasikmalaya, Indonesia - Fahmi Sidiq (Research Collaboration Community (RCC), 2021)
Over-the-counter medicines can be purchased without a doctor's prescription and can be purchased at pharmacies and licensed drugstores to treat non-specific minor illnesses. Limited over-the-counter drugs, also known as list W drugs (W: Waarschuwing = warning/alert) are strong drugs that can be purchased without a doctor's prescription, but their use must pay attention to the drug information on the packaging. The results of this counseling are the mothers of recitation in Cibungur village, Parungponteng sub-district, namely knowing about, how to use, get, store and dispose of good and correct medicines. The selection of over-the-counter and over-the-counter drugs is limited. As well as the characteristics of damaged drugs. people are becoming more careful in the use of drugs. Therefore, the University Pharmacy Study Program takes the initiative to provide community service by providing over-the-counter and limited-free drugs and ways to find out damaged drugs.